1997
DOI: 10.1002/cber.19971300223
|View full text |Cite
|
Sign up to set email alerts
|

On the Ligating Properties of Sulfonate and Perchlorate Anions Towards Zinc

Abstract: Attempts are reported to incorporate sulfonate and perchlo-Tp*Zn-OS0,R. Spectroscopic evidence for perchlorate coorrate anions as ligands in zinc complexes of tripodal ligands. dination in Tp*ZnC104 . 2 DMSO conflicts with crystallograUsing tris(benzimidazolylmethy1)amine (BIMA) only the pic evidence against it in Tp*ZnC104 . ble. Using substituted pyrazolylborates (TpY), the same three NCSH5]C1O4 were determined. sulfonate anions were found to be ligands in the complexes While the coordination chemistry of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 7 publications
5
20
0
1
Order By: Relevance
“…The tetrahedral geometry around a zinc atom was slightly distorted, where the zinc was coordinated by three benzimidazole nitrogen atoms of and one oxygen atom of hydroxide ion with the bond angles around zinc atom 103.7(2)°-114.6(1)°( Table 2). The bond lengths of Zn-N1 2.015 (6) A, Zn-O1 2.047 (7) A are consistent with the literature data of tetrahedral zinc compounds [35,36,40,[45][46][47]. The location of the phenolic OH groups is located at two positions 5 and 6 of each benzene ring (Fig.…”
Section: Hydrolysis Reaction Of Parathion Using [L1zn-(oh 2 )] 2þsupporting
confidence: 88%
“…The tetrahedral geometry around a zinc atom was slightly distorted, where the zinc was coordinated by three benzimidazole nitrogen atoms of and one oxygen atom of hydroxide ion with the bond angles around zinc atom 103.7(2)°-114.6(1)°( Table 2). The bond lengths of Zn-N1 2.015 (6) A, Zn-O1 2.047 (7) A are consistent with the literature data of tetrahedral zinc compounds [35,36,40,[45][46][47]. The location of the phenolic OH groups is located at two positions 5 and 6 of each benzene ring (Fig.…”
Section: Hydrolysis Reaction Of Parathion Using [L1zn-(oh 2 )] 2þsupporting
confidence: 88%
“…The kinetic experiments indicated that the rate of generation of 4-nitrophenolate ion was varied from ester to ester and TpCoOH is the kinetically active species. The hydrolysis of ester occurs via a binuclear mechanism involving the nucleophilic attack of the metal-bound hydroxide to the carbonyl group of the ester as reported by other workers also [38][39][40][41][42][43][44]. The carbonic anhydrase also promotes the hydrolysis of 4-nitrophenylacetate [45] and follows second order kinetics, involving the direct nucleophilic attack at the carbonyl group by a Zn-OH species or hydroxo of other substituted metal ions.…”
Section: Discussionmentioning
confidence: 63%
“…Moreover, we are currently not aware of any zinc hydrosulfide complex that binds the hydrosulfide in a monodentate manner and has an overall charge of +1. For the experimental investigation, we therefore used one example out of the only available class of model compounds for the hydrosulfide analogue of CA, the uncharged complex Tp Ph,Me ZnSH ( 5 ) 18. A slight deviation of the resulting experimental data from the calculated results must therefore be expected.…”
Section: Resultsmentioning
confidence: 99%